Angiopoietin-like protein 4 (ANGPTL4) is an inhibitor of endothelial lipase (EL) while the ANGPTL4/8 complex has reduced EL-inhibitory activity. Issue 9 (September 2021) - Chen, Yan Q.; Pottanat, Thomas G.; Siegel, Robert W.; Ehsani, Mariam; Qian, Yue-Wei; Konrad, Robert J.
Abstract: We previously demonstrated that angiopoietin-like protein 8 (ANGPTL8) forms ANGPTL3/8 and ANGPTL4/8 complexes that increase with feeding to direct fatty acids (FA) toward adipose tissue through differential modulation of lipoprotein lipase (LPL) activity. Each complex correlated inversely with high density lipoprotein cholesterol (HDL) in control subjects. We thus investigated ANGPTL3/8 and ANGPTL4/8 levels in type 2 diabetes patients, who can present with decreased HDL. While ANGPTL3/8 levels in type 2 diabetes patients were similar to those previously observed in normal controls, ANGPTL4/8 levels were roughly twice as high as those in control subjects. Concentrations of ANGPTL3/8 and ANGPTL4/8 in type 2 diabetes patients were inversely correlated with HDL, with the correlation being significant for ANGPTL4/8. We therefore measured the ability of the various ANGPTL proteins and complexes to inhibit endothelial lipase (EL), the enzyme which hydrolyzes phospholipids (PL) in HDL. While confirming ANGPTL3 as an EL inhibitor, we found that ANGPTL4 was a more potent EL inhibitor than ANGPTL3. Interestingly, we observed that while ANGPTL3/8 had increased EL-inhibitory activity compared to ANGPTL3 alone, ANGPTL4/8 exhibited decreased potency in inhibiting EL compared to ANGPTL4 alone. Together, these results show for the first time that ANGPTL4 is a more potent EL inhibitor than ANGPTL3 and suggest a possible reason for why ANGPTL4/8 levels are correlated inversely with HDL. Highlights: ANGPTL4/8 levels are increased in patients with type 2 diabetes. ANGPTL4/8 levels are inversely correlated with HDL in type 2 diabetes patients. ANGPTL4 is an inhibitor of endothelial lipase (EL). ANGPTL4 inhibits EL more potently than ANGPTL3 inhibits EL. ANGPTL4/8 inhibits EL less potently than ANGPTL4 inhibits EL. Abstract : Endothelial lipase; HDL; triglycerides; angiopoietin-like protein; phospholipids; postprandial state